Experience of rehabilitation management in public hospital after it was identified as designated rehabilitation hospital for COVID-19 patients: A qualitative study - Hu, Shuxiao; Chen, Changfu; Yang, Biwen; Liu, Qing; Hu, Han (Frontiers in Public Health, 2022)
Objective: It is essential to focus on the rehabilitation of COVID-19 patients after discharge to prevent their long-term sequelae, but there is less research on healthcare organizations enhancing rehabilitation services for patients discharged from COVID-19. Therefore, this study aimed to describe how a public hospital provides better rehabilitation services for patients after being identified as a designated rehabilitation hospital for pa-tients with COVID-19 and attempted to combine the theory of organizational change to analyze how the hos-pital finally successfully transformed. Methods: A tertiary public hospital located in the center of Xi'an was selected for the study. It was identified as a designated hospital for the rehabilitation of patients discharged from the hospital with COVID-19. 9 hospital leaders and group leaders closely related to the rehabilitation management work were invited to participate in interviews to explore the fact about the hospital's rehabilitation work. The semi-structured interview with the hospital director and the focus group interview with group leaders were used for data collection. Two re-searchers independently conducted a thematic analysis of these responses. Results: 178 primary codes, 22 subcategories, 6 main categories, and 1 core theme were obtained from data analysis. The main categories include organization and coordination (overall deployment, transfer patient, external coordination), hospital infection prevention and control (process transformation, ward disinfection, hospital infection training, inspection, and supervision), staff management (staff classification, closed-loop management, staff health screening), individual services for patients (create an individual scheme, humanistic care, organize special activities, strengthen communication and guidance), comprehensive supporting (basic medical guarantee, daily necessities guarantee, health and nutrition guarantee, assistance fund guarantee) and positive transformation (strategic thinking, benchmarking, strengthen cohesion, expand influence). Conclusions: The hospital had to transform its operations in the face of a complex environment during the pandemic. After deciding to transform, the hospital effectively prevented nosocomial infections and provided rehabilitation services to 583 patients through systematic management measures such as organizational coor-dination, staff classification, and personalized services. In the end, it has been successfully transformed and has grown rapidly. To ensure that it can continue to grow sustainably, the hospital enhanced the new ways that have emerged from this transformation.